Evidence for strong relations between the upper Tagus loess formation (central Iberia) and the marine atmosphere off the Iberian margin during the last glacial period. (May 2021) - Wolf, Daniel; Kolb, Thomas; Ryborz, Karolin; Heinrich, Susann; Schäfer, Imke; Calvo, Ruben; Sanchez, Jesus; Hambach, Ulrich; Zech, Roland; Zöller, Ludwig; Faust, Dominik
Abstract: During glacial times, the North Atlantic region was affected by serious climate changes corresponding to Dansgaard-Oeschger cycles that were linked to dramatic shifts in sea temperature and moisture transfer to the continents. However, considerable efforts are still needed to understand the effects of these shifts on terrestrial environments. In this context, the Iberian Peninsula is particularly interesting because of its close proximity to the North Atlantic, although the Iberian interior lacks paleoenvironmental information so far because suitable archives are rare. Here we provide an accurate impression of the last glacial environmental developments in central Iberia based on comprehensive investigations using the upper Tagus loess record. A multi-proxy approach revealed that phases of loess formation during Marine Isotope Stage (MIS) 2 (and upper MIS 3) were linked to utmost aridity, coldness, and highest wind strengths in line with the most intense Greenland stadials also including Heinrich Events 3–1. Lack of loess deposition during the global last glacial maximum (LGM) suggests milder conditions, which agrees with less-cold sea surface temperatures (SST) off the Iberian margin. Our results demonstrate that geomorphological system behavior in central Iberia is highly sensitive to North Atlantic SST fluctuations, thus enabling us to reconstruct a detailed hydrological model in relation to marine–atmospheric circulation patterns.